2022
DOI: 10.1088/1361-6463/ac4cf7
|View full text |Cite
|
Sign up to set email alerts
|

Chemical vapor deposited WS2/MoS2 heterostructure photodetector with enhanced photoresponsivity

Abstract: Two-dimensional transition metal chalcogenides (TMDCs) have attracted great interest due to their unique semiconductor properties. Among all TMDC materials, MoS2 and WS2 are promising for composing heterostructures. However, traditional TMDC heterostructure fabrication depends on transfer process, with drawbacks of interface impurity and small size. In this work, a two-step chemical vapor deposition (CVD) process was applied to synthesize large-scale WS2/MoS2 heterostructure. Surface morphology and crystal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…2(e), which was apparently longer compared to those reported elsewhere. 17,37,38 The formation of the larger area WS 2 domains not only indicated the effective tuning of the CVD process, but also benefited the further perovskite deposition and photodetector fabrication. The thickness of the WS 2 domain was also measured via AFM, as shown in the inset of Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2(e), which was apparently longer compared to those reported elsewhere. 17,37,38 The formation of the larger area WS 2 domains not only indicated the effective tuning of the CVD process, but also benefited the further perovskite deposition and photodetector fabrication. The thickness of the WS 2 domain was also measured via AFM, as shown in the inset of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It could be found that the monolayer WS 2 and CsSnBr 3 isolated layer revealed PL emissions at 640 and 670 nm, respectively, which were consistent with those reported in the literature. 28,29,37,41 After 10 nm CsSnBr 3 deposition, the WS 2 /CsSnBr 3 heterostructure exhibited both WS 2 and CsSnBr 3 PL emission, with an intensity ratio of 0.455 for I CsSnBr 3 /I WS 2 . With the increase in the thickness of CsSnBr 3 to 50 nm, the PL emission ratio of I CsSnBr 3 /I WS 2 is almost equal.…”
Section: Photophysical Properties Of Ws 2 /Cssnbrmentioning
confidence: 99%
“…136,137 Additionally, molecular beam epitaxy and transfer techniques can also achieve the alternate stacking of different materials. 138,139…”
Section: Heterostructure Strategymentioning
confidence: 99%
“…To attain superior results by fostering coordinated interactions among diverse components Prepared directly 136,137 There is a wide variety of heterogeneous structure combinations Molecular beam epitaxy 138 Transfer techniques 139…”
Section: Heterostructurementioning
confidence: 99%